(untitled) (The Strategic Review for Southern Africa, 2020)
John Daniel, former professor of Political Science at the University of Durban-Westville (UDW), died at his home on 25 July 2014 after a brave struggle with cancer. He will be remembered for the major contribution to political science in South Africa, his activism in the struggle against apartheid, for his inspirational teaching, his work as a progressive editor, and for his important research for the Truth and Reconciliation Commission (TRC).